Contributions to nonlinear elliptic equations and systems : a tribute to Djairo Guedes de Figueiredo on the occasion of his 80th birthday /: a tribute to Djairo Guedes de Figueiredo on the occasion of his 80th birthday. ([2015]) - Unknown
No abstract available